Finding Passion and Life Purpose: Recognize Your Potential for Career Planning - Ana Safitri; Awa Awa; Aulia Aulia; Dwi Rifqa Anggriani; Neza Noviza (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The People Empowerment Program (PRODAMAT) aims to help children of Yatim Putri 'Aisyiyah Yogyakarta Orphanage at the junior and senior high school levels recognize their potential and provide knowledge to the children about career planning. PRODAMAT was held face-to-face (offline) on January 29 and February 4, 2023. PRODAMAT lasted several sessions of activities given to participants, starting from conducting aptitude tests, interests, to knowledge sharing. In the knowledge sharing phase, the material presented was about career planning for orphanage children in the future, and the participants calmly and enthusiastically listened to new knowledge. Based on the post-test score, the children of Yatim Putri 'Aisyiyah Yogyakarta Orphanage at the junior and senior high school level experienced an increase of 5.9 after the knowledge sharing. This shows that there is an increase in children's insights after doing knowledge sharing because children get new insights related to interests that exist in themselves for career planning.